Safety and Feasibility of Electrochemotherapy of the Pancreas in a Porcine Model. Issue 9 (October 2020) - Dežman, Rok; Čemažar, Maja; Serša, Gregor; Seliškar, Alenka; Erjavec, Vladimira; Trotovšek, Blaž; Gašljevič, Gorana; Bošnjak, Maša; Lampreht Tratar, Urša; Kos, Bor; Djokić, Mihajlo; Milevoj, Nina; et al.
Abstract : Objectives: The use of thermal ablative therapies in the pancreatic tumors is limited because of the risk of the vessel injury and potential pancreatitis or fistula formation. Electrochemotherapy (ECT) is an ablative therapy with an established role in the treatment of cutaneous and liver tumors. This study was designed to evaluate the safety and feasibility of ECT of the pancreas in a porcine survival model. Methods: In the first group, 4 animals underwent computed tomography (CT)–guided percutaneous ECT with bleomycin of the pancreatic tail. In the second group (4 animals), the intraoperative ECT with bleomycin of pancreatic tail and head was performed. Animals were followed for 7 days and then killed. Clinical parameters, CT imaging, laboratory, and histologic analysis were performed. Results: All pigs survived the ECT procedure and none of them developed clinical signs of acute pancreatitis or related complications. There were no signs of acute pancreatitis or damage to the large vessels present in the follow-up CT scans. No significant change in laboratory parameters was obtained after procedure. Conclusions: This study shows that ECT with bleomycin is feasible and safe in the pancreatic parenchyma. Clinical studies are needed to evaluate the efficacy of ECT in pancreatic cancer.